Religious Culture In Korean Peninsula - Chathurika Vivanthi Diddeniya, J.; Isurika Dilanthi Diddeniya, J. (University of jaffna, 2018)
Asia is rich with its own languages, history, traditions and religions. This variety can be seen in the lives of Asian people special in their culture. Korean peninsula is geographically located in an important location in Asia, in between China and Japan. Korea has a wide variety of religious elements such as Buddhism, Confucianism, Christianity and Protestantism etc. Among traditional religions, Christianity was also rooted in Korean society. This study examines how Christianity affects Korea for its political, economical and social changes. Although Korea was influenced by Buddhism, Shamanism, and Confucianism historically, Christianity became very popular since end of 20 th century. Consequently, 27% of the population believes in Christianity (including Catholic and protestant). After the Korean War, the state religion was changed slowly to Christianity. But, there are no religious conflicts occurred up to now. This is an interesting fact, because this Kind of religious Composition is not rare in the other countries. In the middle of the 18 th century Christianity became the state religion. At that time, Christianity was successfully roots in Korea. In early periods Shamanism, Buddhism and Confucianism rooted as traditional religions in Korea. Koreans believe that Christianity showed Korea the way to become a developed country. For an example, church was intruded in helping, which could turn Korea into a more democratic country. As a result of this, Christian population in Korea society was rapidly increased. Traditional Koran society was arranged according to the principles of Confucianism. But, after introducing Christianity, traditional Korean society was changed to a one which has much freedom in mind. Christians believe that their values have had a positive effect on various social relations. As a conclusion Korea is a dynamic country with variety of religious environment. It is a wonderful fact that existence of both Eastern and Western very peacefully.
Keywords: Coexist; Christianity; Korea; Multi religious culture